2021
DOI: 10.1111/jth.15218
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism incidence among patients recommended for pharmacologic thromboembolism prophylaxis after cesarean delivery in selected guidelines

Abstract: Background Multiple guidelines regarding risk stratification for venous thromboembolism (VTE) incidence following cesarean delivery have been promulgated. Objective To estimate the percentage of cesarean delivery patients for which pharmacologic VTE would be recommended and subsequent incidence of VTE, based on several guidelines. Patients/Methods This retrospective cohort study used data from the Nationwide Readmissions Database from October 2015 through December 2017. Diagnosis and procedure codes were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…13 For these analyses, ICD-9-CM codes were translated to ICD-10-CM codes using the publicly available General Equivalence Mappings provided by the Centers for Medicare & Medicaid Services and National Center for Health Statistics, and by reviewing prior research. 9,14 This study had three objectives. The first objective was to determine temporal trends in rate of VTE during delivery hospitalizations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 For these analyses, ICD-9-CM codes were translated to ICD-10-CM codes using the publicly available General Equivalence Mappings provided by the Centers for Medicare & Medicaid Services and National Center for Health Statistics, and by reviewing prior research. 9,14 This study had three objectives. The first objective was to determine temporal trends in rate of VTE during delivery hospitalizations.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, there are limited data on obstetric VTE trends after 2014. 9 Given that addressing knowledge gaps related to VTE risk may be of clinical significance, the objectives of this study were to characterize temporal trends in VTE during delivery hospitalizations, temporal trends in common obstetric and medical risk factors for VTE, and the relationship between risk factors and likelihood of VTE events.…”
mentioning
confidence: 99%
“…13 In a large US database study of over 1.2 mil lion cesar ean deliv er ies, patients who were iden ti fied as "ele vated risk" by the 2018 ASH guide lines had an actual VTE inci dence of 20.0 (14.9-25.7) per 1000 cesar ean deliv er ies (2% risk) at 6 weeks post par tum, whereas other clin i cal prac tice guide lines' "high-risk" categories had lower actual VTE inci dences (Table 2). 22 In con trast, in a sin gle-cen ter study, the highest cal cu lated VTE risk was approx i ma tely 0.5% using a risk score derived by Sultan et al 31 , which is lower than the VTE risk threshold cutoff suggested by the ASH guidelines. 23 There have been preg nancy and post par tum VTE risk scores derived and exter nally val i dated from large reg is try data bases, but these scores have yet to be stud ied pro spec tively or incorpo rated into guide lines.…”
Section: Clinical Casementioning
confidence: 92%
“…Currently, guidelines suggest to risk stratify using empiric schemes of levels or combination of risk factors in several categories: no thromboprophylaxis or mechanical thromboprophylaxis only, short-term pharmacologic thromboprophylaxis (days) and 6-weeks of pharmacologic thromboprophylaxis. Importantly, such guidelines (ACOG ( 26 ), RCOG ( 27 ), ASH ( 24 )), which are detailed elsewhere, diverge dramatically in the proportion of women with advised thromboprophylaxis, between 7 and 40% for all deliveries ( 28 ) and 0.2–73% for cesarean deliveries ( 29 ). Logically, a higher prevalence of use of thromboprophylaxis is associated with lower risks among those with thromboprophylaxis, and greater numbers needed to treat to prevent 1 VTE.…”
Section: Risk Stratificationmentioning
confidence: 99%